2011
DOI: 10.1542/peds.2010-3852
|View full text |Cite
|
Sign up to set email alerts
|

Fever and Antipyretic Use in Children

Abstract: Fever in a child is one of the most common clinical symptoms managed by pediatricians and other health care providers and a frequent cause of parental concern. Many parents administer antipyretics even when there is minimal or no fever, because they are concerned that the child must maintain a “normal” temperature. Fever, however, is not the primary illness but is a physiologic mechanism that has beneficial effects in fighting infection. There is no evidence that fever itself worsens the course of an illness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
313
0
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(344 citation statements)
references
References 89 publications
(83 reference statements)
7
313
0
15
Order By: Relevance
“…A key concern in these studies is how infection is defined and reported. In children, fever is an almost universal sign of infection, and other causes of elevated body temperature are rare in temperate countries (Sullivan and Farrar 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A key concern in these studies is how infection is defined and reported. In children, fever is an almost universal sign of infection, and other causes of elevated body temperature are rare in temperate countries (Sullivan and Farrar 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In case of using high dose of rectal acetaminophen (30 mg/kg) in children at high risk for fever, this high dose should be used just once and repeating the same doses should be avoided because more efficacies has not been proven and the risk of increased cumulative doses and poisoning will be followed. It should be noted that the maximum daily-allowed dose of acetaminophen is 90 mg/kg for up to 3 consecutive days or 75 mg/kg for longer use [3,15].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, fever in 2% to 4% of children aged 6 months to 5 years can cause seizures. Therefore, the fever should be controlled as soon as possible in children with the above-mentioned risk factors, although in other children, control of the fever with a rectal degree temperature of 39ºC or when the child feels uncomfortable, is recommended [2,3]. However, Ibuprofen is similarly or more efficacious than acetaminophen for treatment of pain and fever in adults and children and was equally safe, yet still, Acetaminophen is considered as first-line therapy for the treatment of fever and mild-to-moderate pain in infants and children according to international guidelines and recommendations [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, students often find it hard to conceptually distinguish host defenses (e.g., fever) from true pathological defects (e.g., seizures) in disease. For example, while fever was once viewed as pathological, current recommendations advocate against treating fever in children (Sullivan and Farrar 2011), correctly noting that "fever…is not the primary illness but is a physiologic mechanism that has beneficial effects in fighting infection." Fever is increasingly viewed as an adapted facultative response (Kluger et al 1996).…”
Section: Discussionmentioning
confidence: 99%